Feasibility study of paclitaxel plus carboplatin in patients with endometrial cancer: A Japan Kanto Tumor Board study (JKTB trial). Issue 1 (28th May 2012) - Yamada, Kyosuke; Tanabe, Hiroshi; Imai, Manami; Jobo, Toshiko; Kudo, Kazuya; Fujiwara, Hiroyuki; Nagata, Chie; Furuya, Kenichi; Suzuki, Mitsuaki; Ochiai, Kazunori; Tanaka, Tadao; Yasuda, Makoto
Abstract Aim: The optimal chemotherapy regimen for patients with endometrial cancer has not been established. We assessed the feasibility of paclitaxel plus carboplatin (TC) for postoperative chemotherapy in patients with endometrial cancer. Material and Methods: Patients with newly diagnosed endometrial cancer received TC (paclitaxel 180 mg/m2, carboplatin AUC6 mg/mL/min) every three weeks. Treatment was continued until disease progression or completion of six cycles. Toxicities were evaluated every cycle according to NCI‐CTCAE version 3.0. Results: Sixty patients were registered from December 2005 through November 2006. Forty‐four of 60 (73.3%) cases completed all of the planned six cycles. Grades 3 and 4 hematologic toxicities were observed as follows: leukopenia (61.7%), neutropenia (95.0%), anemia (21.7%), and thrombocytopenia (5.0%). There were six patients who dropped out from the protocol by neutropenia. Grade 3 non‐hematologic toxicities were observed as follows: nausea (3.3%), vomiting (1.7%), neuropathy (5.0%), myalgia (6.7%) and constipation (1.7%). No grade 4 non‐hematologic toxicity was observed. Conclusion: This TC regimen is feasible for endometrial cancer patients.